2022
DOI: 10.1002/nur.22262
|View full text |Cite
|
Sign up to set email alerts
|

International migration and its influence on health

Abstract: What would it take for you to leave your home and everything you know? What if you left knowing you might not be able to return? If you had to leave quickly, what would you take with you? These are questions that many immigrants must grapple with because of their circumstances. Before the COVID-19 pandemic, the global migration of humans had reached the highest levels in recorded human history.International Organization for Migration (IOM) is the global institution that studies and helps inform international l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Therefore, it is suggested that if interviews cannot be carried out in the participant’s native language, the use of interpreters is preferably adopted. However, the qualifications, timing, employment, duties, and training of interpreters used in the study must be planned well in advance ( 18 ) .…”
Section: Communication and Languagementioning
confidence: 99%
“…Therefore, it is suggested that if interviews cannot be carried out in the participant’s native language, the use of interpreters is preferably adopted. However, the qualifications, timing, employment, duties, and training of interpreters used in the study must be planned well in advance ( 18 ) .…”
Section: Communication and Languagementioning
confidence: 99%
“…Upward trends in immigration are expected to continue. Various factors drive human migration, with war, civil unrest and violence, and economic precarity among the top factors driving people to leave their homes (Squires et al, 2022). For those who are eligible to become citizens, the path can take many years.…”
Section: An Overview Of Recent Migration Trends In the United States ...mentioning
confidence: 99%
“…The necessity and importance for an enhanced understanding of the impact of language barriers on the patient attempting to access and use health services in the US is driven by the significant growth of the immigrant population in the country. Since 1990, the immigrant population in the US grew from approximately 8% of the population to nearly 14% before the pandemic in 2019 [ 29 ]. Healthcare organizations that previously had minimal to no experience serving immigrant populations, including those with language barriers, now often find themselves working with a rapidly growing community which has a diverse range of health care needs and may lack the resources or understanding of the extent to which language barriers affect the patient experience and health outcomes.…”
Section: Introductionmentioning
confidence: 99%